The Analysis of Light Intensity Transmission Coefficient Through Plastic Fibers for the Design of Closed Room Lighting without Electricity - Taat Guswantoro (International Journal of Science and Society, 2021)
The phenomenon of total internal reflection can be used to guide the light to be transmitted from one place to another, it is applied to the guiding principle of light in fiber optics. A fiber rope made of clear plastic material with a uniform refractive index, when one end fired a beam of light then the light will be forwarded along the strap so that out at the other end. This principle can be applied as a lighting source in a closed room by passing light from the outdoors by using plastic fiber, so it doesn’t need the electricity. In this study, theoretical analysis of the percentage of the intensity of light transmitted by the fiber plastic succeed as a function of the refractive index and determine the transmission coefficient for some plastic seeds are eligible to be used as a plastic fiber light successor. From the results of deriving the equation, the light transmission coefficient of plastic is and the terms of plastic seeds that can be used as a plastic fiber are having a refractive index . Based on refractive index data from profesionalplastics, the maximum transmission coefficient value for Ethylene Tetrafluoro Ethylene Copolymer is 82.23% and the minimum transmission value of Fluorinated Ethylene Propylene Copolymer is 55.99%.